IMPLEMENTATION OF THE SCIENTIFIC APPROACH ON THE THEMATIC LEARNING (Case Study of Al-Zahra Pamulang Islamic Elementary School) - Fauzan Fauzan; Nurul Mawaddah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
This research has a goal, namely to find alternative solutions for teachers in implementing a scientific approach to thematic learning at Al-Zahra Elementary School Indonesia, Pamulang. This study used descriptive qualitative method. Data collection and processing techniques use observation, interviews and document analysis. The procedure for collecting and processing data passes through 3 stages, namely the preparation stage, the implementation stage, and the final stage. Data analysis techniques are data reduction, data display/data presentation, and drawing conclusions. Integrated thematic learning using a scientific approach in grade 2 SD Al-Zahra Indonesia is in the fairly good category. As for the process of making the RPP can be said to be good. However, there are some student activities during learning that the teacher has not been able to deal with. For future improvements, the solution that can be given or submitted by researchers to schools / homerooms in improving the quality of the scientific approach in thematic learning is to hold training in making lesson plans in order to maximize the quality of lesson plans made by teachers. Schools should also regularly hold advanced training on the implementation of thematic learning so that teachers have deeper insight and knowledge to apply in the classroom. Keywords: scientific approach; solutions; thematic learning